Investigation of Problematic Internet Usage of University Students With Psychosocial Levels at Different Levels - Eroglu, Mehmet; Pamuk, Mustafa; Pamuk, Kubra (Elsevier Science Bv, 2013)
The aim of this study is to analyse problematic internet usage of university students according to pyscho-social features (loneliness and shyness) and gender. Survey model is used for this research, To collect data; personel information form, problematic internet usage scale, UCLA-loneliness scale and shyness scale were applied for 601 students who are from different Departments of Faculty of Education at Firat University. To analyse these data correlation, t test, one way variance (ANOVA) analysis and Scheffe test were used. Results revealed that problematic internet usage was significantly associated with loneliness (r=.35) and shyness (r=.31). Furthermore, there were significant differences between problematic internet usage and independent variables (gender, loneliness and shyness). The results of the study were discussed together with the results of different studies and suggestions were made. (C) 2013 The Authors. Published by Elsevier Ltd.
13th International Educational Technology Conference -- OCT 30-NOV 01, 2014 -- Lisbon, PORTUGAL
Keywords: Problematic internet usage; loneliness; shyness